Effect Of Education And Training On Employee Performance At The Education Office Aceh Tamiang Regency - Suci Widana (IHSA Institute, 2021)
This study aims to determine the magnitude of the effect of education and training on employee performance at the Aceh Tamiang District Education Office. This study uses a correlational method using quantitative data analysis and statistical formulas. The sample of this study was the employees of the Aceh Tamiang District Education Office who had attended education and training (Diklat) in 2005-2016, amounting to 82 people. Questionnaires are used to measure education and training variables and employee performance, while interviews and observations are used to support research data. The data analysis techniques used are validity test, reliability test, normality test, simple regression analysis, significant test and determinant coefficient. The results showed that education and training had a positive and significant influence on employee performance and the effect was in the high category as indicated by the regression equation Y = 22,933 + 0.464X with a significant test (tcount) of 7.736, coefficient of determination (r2xy) of 0.428. Based on the coefficient of determination (r2xy) 0.428, it means that 42.8% of employee performance is influenced by education and training of employees while the remaining 57.2% is influenced by other variables not examined in this study. coefficient of determination (r2xy) of 0.428. Based on the coefficient of determination (r2xy) 0.428, it means that 42.8% of employee performance is influenced by education and training of employees while the remaining 57.2% is influenced by other variables not examined in this study. coefficient of determination (r2xy) of 0.428. Based on the coefficient of determination (r2xy) 0.428, it means that 42.8% of employee performance is influenced by education and training of employees while the remaining 57.2% is influenced by other variables not examined in this study.